Lost in space : geographies of science fiction - Kitchin, Rob; Kneale, James (Continuum, 2002)
Science fiction - one of the most popular literary, cinematic and televisual genres - has received increasing academic attention in recent years. For many theorists science fiction opens up a space in which the here-and-now can be made strange or remade; where virtual reality and cyborg are no longer gimmicks or predictions, but new spaces and subjects. Lost in space brings together an international collection of authors to explore the diverse geographies of spaceexploring imagination, nature, scale, geopolitics, modernity, time, identity, the body, power relations and the representation of.